Whole family-based physical activity promotion intervention: the Families Reporting Every Step to Health pilot randomised controlled trial protocol - Esther van Sluijs; Helen Elizabeth Brown; Justin M Guagliano; Emma Coombes; Elizabeth S Haines; Claire Hughes; Andrew P Jones; Katie L Morton (BMJ Open)
Introduction Family-based physical activity (PA) interventions present a promising avenue to promote children’s activity; however, high-quality experimental research is lacking. This paper describes the protocol for the FRESH (Families Reporting Every Step to Health) pilot trial, a child-led family-based PA intervention delivered online.Methods and analysis FRESH is a three-armed, parallel-group, randomised controlled pilot trial using a 1:1:1 allocation ratio with follow-up assessments at 8 and 52 weeks postbaseline. Families will be eligible if a minimum of one child in school Years 3–6 (aged 7–11 years) and at least one adult responsible for that child are willing to participate. Family members can take part in the intervention irrespective of their participation in the accompanying evaluation and vice versa.Following baseline assessment, families will be randomly allocated to one of three arms: (1) FRESH; (2) pedometer-only or (3) no-intervention control. All family members in the pedometer-only and FRESH arms receive pedometers and generic PA promotion information. FRESH families additionally receive access to the intervention website; allowing participants to select step challenges to ‘travel’ to target cities around the world, log steps and track progress as they virtually globetrot. Control families will receive no treatment. All family members will be eligible to participate in the evaluation with two follow-ups (8 and 52 weeks). Physical (eg, fitness and blood pressure), psychosocial (eg, social support) and behavioural (eg, objectively measured family PA) measures will be collected at each time point. At 8-week follow-up, a mixed methods process evaluation will be conducted (questionnaires and family focus groups) assessing acceptability of the intervention and evaluation. FRESH families’ website engagement will also be explored.Ethics and dissemination This study received ethical approval from the Ethics Committee for the School of the Humanities and Social Sciences at the University of Cambridge. Findings will be disseminated via peer-reviewed publications, conferences and to participating families.Trial registration number ISRCTN12789422